NOMS 2020 - 2020 IEEE/IFIP Network Operations and Management Symposium 2020
DOI: 10.1109/noms47738.2020.9110422
|View full text |Cite
|
Sign up to set email alerts
|

5G QoS: Impact of Security Functions on Latency

Abstract: Network slicing is considered a key enabler to 5th Generation (5G) communication networks. Mobile network operators may deploy network slices-complete logical networks customized for specific services expecting a certain Quality of Service (QoS). New business models like Network Slice-as-a-Service offerings to customers from vertical industries require negotiated Service Level Agreement (SLA) contracts, and network providers need automated enforcement mechanisms to assure QoS during instantiation and operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Our testbed offers researchers a high degree of freedom to design and execute experiments, with user-controlled scripts and root access on the experiment nodes. We used pos in the past for entirely different experiments: distributed network experiments involving 15 nodes [34], low-latency analysis of single network nodes [18], and as a mere development environment for packet processing software [16]. As a testbed, the capabilities of pos neither stand out nor back compared with its main competitors [9,20,28].…”
Section: Testbed Vs Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Our testbed offers researchers a high degree of freedom to design and execute experiments, with user-controlled scripts and root access on the experiment nodes. We used pos in the past for entirely different experiments: distributed network experiments involving 15 nodes [34], low-latency analysis of single network nodes [18], and as a mere development environment for packet processing software [16]. As a testbed, the capabilities of pos neither stand out nor back compared with its main competitors [9,20,28].…”
Section: Testbed Vs Methodologymentioning
confidence: 99%
“…One of the essential elements of a network experiment is the used traffic source. Typical experiments in our testbed use synthetic traffic created at runtime by a packet generator [17,18,30]. However, other experiments use pcaps of recorded traffic.…”
Section: Loadgen Dut Controllermentioning
confidence: 99%
“…They propose a synchronized programming model to simplify application development for low-latency applications. In previous work [2,3], we demonstrated that high reliability and low latency could be achieved on off-the-shelf hardware and virtualized systems, using a DPDK-accelerated Snort. However, the latency was still subject to interrupts causing latency spikes in the s-range.…”
Section: Background and Related Workmentioning
confidence: 96%
“…Despite these previous works, only few studies analyze from a quantitative and scientific point of view the impact of security mechanisms on URLLC. However, their general conclusion is that virtualization-based networks cannot easily support URLLC, and bare metal schemes must be preferred [19]. This approach, nevertheless, evolves contrary to market tendencies (more focused on software-defined networks).…”
Section: G Security Solutions and Analysis Frameworkmentioning
confidence: 99%
“…If these errors go above a certain limit b CRC (associated to the maximum number of errors that may be corrected through Cyclic Redundancy Codes), they force the packet to be discarded. Furthermore, in all modern communication systems, encoded and modulated signals are polar non return to zero (polar NRZ) sources, so the Bit Error Rate (BER) caused by physical noise may be calculated using the complimentary error function erfc (•) (19). Then, the probability of a packets to be discarded in a link P P because of physical noise can be deducted (20).…”
Section: G Core and Ran Implementations: Analytical Modelsmentioning
confidence: 99%